Body Mass Index in Multiple Sclerosis: Associations with CSF Neurotransmitter Metabolite Levels. (24th September 2013) - Markianos, Manolis; Evangelopoulos, Maria-Eleftheria; Koutsis, Georgios; Davaki, Panagiota; Sfagos, Constantinos
Abstract : Body weight and height of patients with relapsing-remitting multiple sclerosis (RRMS) or clinically isolated syndrome suggesting MS (CIS) in the age range 18 to 60 years (154 males and 315 females) were compared with those of subjects (146 males and 212 females) free of any major neurological disease. In drug-free patients, CSF levels of the metabolites of noradrenaline (MHPG), serotonin (5-HIAA), and dopamine (HVA), neurotransmitters involved in eating behavior, were estimated in searching for associations with body mass index (BMI). Statistical evaluations were done separately for males and females. Lower BMI was found in female MS patients compared to female controls, more pronounced in RRMS. BMI was not associated with duration of illness, smoking, present or previous drug treatment, or disability score. Body height showed a shift towards greater values in MS patients compared to controls. Patients in the lower BMI quartile (limits defined from control subjects) had lower 5-HIAA and HVA compared to patients in the upper quartile. The results provide evidence for weight reduction during disease process in MS, possibly related to deficits in serotoninergic and dopaminergic activities that develop during disease course, resulting in impairments in food reward capacity and in motivation to eat.